FAST TRACK SURGERY IN TOTAL KNEE ARTHROPLASTY - A REVIEW. - Pencho Kosev; Tsvetan Sokolov; Ivalinka Pavlova; Boyan Valentinov; Jordan Andonov; Neli Petrova (Peytchinski Publishing, 2015)
The number of orthopedic surgeons who are convinced in the need for significant changes in planned total knee arthroplasty (TKA) is increasing slowly and steadily. A new approach to pain control has been developed over the past 10-15 years, and the introduction of techniques to reduce perioperative stress, and the use of minimally invasive surgical techniques can help limit postoperative complications and shorten recovery time. This type of optimization is regarded as Fast-track Care program, where improved healing process is particularly useful to comorbid patients.